Nickel/Brønsted acid dual-catalyzed regio- and enantioselective hydrophosphinylation of 1, 3-dienes: access to chiral allylic phosphine oxides. Issue 5 (13th January 2022) - Long, Jiao; Li, Yuqiang; Zhao, Weining; Yin, Guoyin
Abstract : Asymmetric hydrophosphinylation of 1, 3-dienes with phosphine oxides using an inexpensive chiral catalyst has been demonstrated, providing access to chiral allylic phosphine oxides with broad substrate scope and high regio- and enantioselectivity. Abstract : While chiral allylic organophosphorus compounds are widely utilized in asymmetric catalysis and for accessing bioactive molecules, their synthetic methods are still very limited. We report the development of asymmetric nickel/Brønsted acid dual-catalyzed hydrophosphinylation of 1, 3-dienes with phosphine oxides. This reaction is characterized by an inexpensive chiral catalyst, broad substrate scope, and high regio- and enantioselectivity. This study allows the construction of chiral allylic phosphine oxides in a highly economic and efficient manner. Preliminary mechanistic investigations suggest that the 1, 3-diene insertion into the chiral Ni–H species is a highly regioselective process and the formation of the chiral C–P bond is an irreversible step.